2022
DOI: 10.1136/emermed-2021-211946
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors for testicular torsion and a warning against falsely reassuring ultrasound scans: a 10-year single-centre experience

Abstract: BackgroundWe sought to determine which demographic, clinical and ultrasonography characteristics are predictive of testicular torsion (TT) and to determine factors associated with time to treatment.MethodsWe retrospectively reviewed all medical records of patients (0–17 years) with acute scrotal syndrome (ASS) who were treated in our hospital in Lithuania between 2011 and 2020. We extracted patients’ demographic data, in-hospital time intervals, clinical, US and surgical findings. TT was determined at surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Nonspecific symptoms such as inguinal swelling and pain, scrotal swelling, abdominal pain, and nausea or vomiting might delay the management of TT beyond 6 hours. 2,13,19,38 We attributed the good outcomes in our patients with TT to undergoing surgery shortly beyond 6 hours due to the good hospital access, comprehensive population coverage, and short waiting times, as well as prompt urology consultation. 40 Research has evaluated the predictors of TS in children with TT, 12,17 and we identified several risk factors associated with orchiectomy in children with TT in a multivariate analysis, including a longer interval between SP onset and PED arrival, 13,36,37 absent TUBF, 1,3,7,8,16,17,[31][32][33][34] interval between SP onset and surgery of more than 24 hours, 2,7,8,16 and a greater degree of TT.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Nonspecific symptoms such as inguinal swelling and pain, scrotal swelling, abdominal pain, and nausea or vomiting might delay the management of TT beyond 6 hours. 2,13,19,38 We attributed the good outcomes in our patients with TT to undergoing surgery shortly beyond 6 hours due to the good hospital access, comprehensive population coverage, and short waiting times, as well as prompt urology consultation. 40 Research has evaluated the predictors of TS in children with TT, 12,17 and we identified several risk factors associated with orchiectomy in children with TT in a multivariate analysis, including a longer interval between SP onset and PED arrival, 13,36,37 absent TUBF, 1,3,7,8,16,17,[31][32][33][34] interval between SP onset and surgery of more than 24 hours, 2,7,8,16 and a greater degree of TT.…”
Section: Discussionmentioning
confidence: 98%
“…The numbers of patients needing surgery, surgically confirmed TT, orchiopexy, orchiectomy, hospital admission, and hospital length of stay (LOS) were also evaluated. Testicular torsion-associated symptoms were defined as inguinal swelling and pain, scrotal skin erythema or dark color, scrotal swelling, scrotal tenderness, a hard testis on palpitation, abdominal pain, and nausea or vomiting 2,13,19 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations